Three-dimensional electrode of Ni/Co layered double hydroxides@NiCo2S4@graphene@Ni foam for supercapacitors with outstanding electrochemical performance. (10th September 2015) - Tao, Yan; Ruiyi, Li; Lin, Zhou; Chenyang, Ma; Zaijun, Li
Graphical abstract: We reported a new strategy for fabricating three-dimensiona electrode of Ni/Co layered double hydroxide@NiCo2 S4 @graphene@Ni foam for supercapacitors. The resulting 3D electrode offers a jungle-like architecture. The unique structure creates ultra fast electron transfer and electrolyte transport as well as the maximum utilization rate of the space and the surface. The electrode exhibits a prominent advantage of high specific capacitance, high-current capacitive behaviour and cycle stability. Highlights: The study developed a new strategy for fabricating 3D electrode of Ni/Co-LDH@NiCo2 S4 @G. The as-prepared 3D electrode offers a jungle-like architecture. The unique structure creates an efficient conduction network and high mass loading. The electrode achieves significantly synergetic effect among different materials. The electrode exhibits an excellent electrochemical performance for supercapacitors. ABSTRACT: Great challenge for the fabrication of free-standing three-dimensional electrode still remains to simultaneously achieve high specific capacitance, rate performance and cycle stability. The paper reprted a new three-dimensional (3D) electrode of Ni/Co layered double hydroxide@NiCo2 S4 @graphene@Ni foam (Ni/Co-LDH@NiCo2 S4 @G) for supercapacitors. The as-prepared 3D electrode offers an unique architecture, which create an efficient conduction network and maximum utilization of space and interface. The graphene acts as well-knit and conductive skin coated on the skeleton of Ni foam for growing NiCo2 S4 . The conductive NiCo2 S4 array serves as bridge between Ni/Co-LDH and graphene, leading to ultrafast electron transfer and electrolyte transport. A slew of splits and holes existing in the NiCo2 S4 array play one role as the ion-reservoir to contain host of electrolyte ions. To evaluate the feasibility of 3D electrode's application in supercapacitors, the electrochemical performance was investigated by using the three-electrodes test system and two-electrodes test system, respectively. The 3D electrode exhibits high specific capacitance (2001.2 F g −1 ), big areal capacitance (15.21 F cm −2 ), high rate capability (1645.6 F g −1 at the current density of 8 A g −1 ) and prominent synergetic effect (more than 1.6-fold that of the theoretical capacitance) in a three-electrode test system with 3 M KOH electrolyte. Interestingly, the addition of K3 Fe(CN)6 into the KOH electrolyte further enhances the pseudocapacitance via both directly contributing pseudocapacitance to the Ni/Co-LDH@NiCo2 S4 @G and promoting electron gain and loss of Co and Ni ions. The specific capacitance increases to 6282.6 F g −1 at the current density of 6 A g −1 . The asymmetric supercapacitor of Ni/Co-LDH@NiCo2 S4 @G/activated carbon provides the energy density of 102.8 W h kg −1 at the power density of 800 W kg −1 in the two-electrodes test system, which is close to that of lithium ion battery. Such a large capacitive performance make it can be used as promising electrode materials for next-generation high-performance supercapacitors.